SYNERGY: ADAPTABILITY CONCEPT IN MANAGERIAL DECISIONS - ACCOUNTANT’S PERSPECTIVE - Omah Ishmael (European Scientific Journal, ESJ, 2012)
Purpose: The objective of this paper is to highlight the conceptual terminology of synergy, its meritorious advantage in managerial decision analysis, the challenges in applying synergy ideology to harness its benefits to the advantage of the organizational profitability, the environmental constraints which limit its adaptability to the detriment of organizational performance.